(3GdeNJUQ aj Gdabgs - (3YHO GdQMef Hf eMeO Hf YGeQ GdCNVQj, CHhRjO,J (B983 (3g` s
(3ChdgG (B:s
(3Chd eG jLH Ydi JUMjM EjeGfg Ke eYQaI s
(3BNQgG (B:s
(3aJQc jbjfg hjQLY Edjge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B187s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ShOGf jhfjSch s
Keywords: (3CUhd Gdabgs